Career Planning Education for High School Students in Kecamatan Limo, Depok - Alnisa Min Fadlillah; Dienni Ruhjatini (MITRA: Jurnal Pemberdayaan Masyarakat, 2019)
The present community service program was motivated by a number of problems faced by employees, especially those who had just entered the workforce. They were confused in determining their career levels. As a result, they held the position that they did not like. This condition affected their career developments. It could hinder their performance and job satisfaction so that in the end the company might be harmed. Therefore, the present activity aimed to educate high school students about the importance of early career planning. The program was given to grade X high school students in Limo District, Depok, West Java. The activity was implemented in two meetings. The methods used included lectures, discussion, question and answer sessions, and career planning practice. Participants were also invited to explain the results of their career planning. The results of evaluation of 78 students in general shows increasing knowledge about self-understanding, self-preparation, introduction to the world of work, and future planning.